2018
DOI: 10.1039/c8tx00034d
|View full text |Cite
|
Sign up to set email alerts
|

Is tartrazine really safe?In silicoandex vivotoxicological studies in human leukocytes: a question of dose

Abstract: The use of food colorings has a long-recorded history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Our findings were consistent with Khan et al (2020), who observed optimum aberration when meristematic cells of onion roots were treated with a 1% concentration of red azo FCA then 1% metanil yellow azo FCA for 48 h. Further, the red azo FCA inhibited more mitotic index and induced chromosomal breaks, disorientation at metaphase, C-mitosis, sticky metaphase, sticky anaphase, and bridge anaphase (Khan et al, 2020). Likewise, Floriano et al (2018), reported that the tartrazine in a minute quantity like 70 µg mLˉ1 concentration induced DNA damages in ex vivo human leukocytes culture. According to ADMET software, the 1000000 µg Lˉ1 concentration of azo FCA may be killed 50% of the tested organism (Floriano et al, 2018).…”
Section: Microscopic Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings were consistent with Khan et al (2020), who observed optimum aberration when meristematic cells of onion roots were treated with a 1% concentration of red azo FCA then 1% metanil yellow azo FCA for 48 h. Further, the red azo FCA inhibited more mitotic index and induced chromosomal breaks, disorientation at metaphase, C-mitosis, sticky metaphase, sticky anaphase, and bridge anaphase (Khan et al, 2020). Likewise, Floriano et al (2018), reported that the tartrazine in a minute quantity like 70 µg mLˉ1 concentration induced DNA damages in ex vivo human leukocytes culture. According to ADMET software, the 1000000 µg Lˉ1 concentration of azo FCA may be killed 50% of the tested organism (Floriano et al, 2018).…”
Section: Microscopic Analysissupporting
confidence: 90%
“…Likewise, Floriano et al (2018), reported that the tartrazine in a minute quantity like 70 µg mLˉ1 concentration induced DNA damages in ex vivo human leukocytes culture. According to ADMET software, the 1000000 µg Lˉ1 concentration of azo FCA may be killed 50% of the tested organism (Floriano et al, 2018). Furthermore, the toxicological studies of these azo FCAs revealed interference in the hydrogen bonds of chromosomes which caused oxidative stress and allergic responses (Kashanian and Zeidali, 2011).…”
Section: Microscopic Analysismentioning
confidence: 96%
“…28 As the oral absorption of azo dyes is 2% to 5% in humans, their mean amount reaching the blood for an adult weighting 70 kg (7% of body weight, as well as 5 L of blood) would be approximately 2.1 to 5.25 mg/mL. [29][30][31] Therefore, the zebrafish-exposed concentrations (0-53.4 mg) of azo dyes used in our study were higher than the expected human exposures at the ADI.…”
Section: Discussionmentioning
confidence: 99%
“…• Decreased activity of Superoxide Dismutase (SOD), Catalase (CAT), considering that there was a decline in Glutathione-Stransferase (GST) Glutathione Reductase (GR); • Levels of ADI in the dye affect and alter biochemical markers of brain tissues and cause oxidative damage. Floriano et al (2018) To evaluate the cytotoxicity and genotoxicity of tartrazine in human leukocyte culture.…”
Section: Basu Andmentioning
confidence: 99%